Adsorption Properties and Quantum Molecular Descriptors of the Anticancer Drug Cytophosphane on the Armchair Single-Walled Carbon Nanotubes: A DFT Study - Felegari, Zahra; Hamedani, Shahla (Letters in Organic Chemistry, 2022)
In the current work, the adsorption of cytophosphane (cytophosphane is a chemotherapeutic drug and is used to treat several specific autoimmune diseases and malignant processes) on the (5,5) SWCNT was studied using density functional theory (DFT) calculations in terms of geometry, energy gap, charge transfer, molecular electrostatic potential surface, and density of state analysis. The behavior of the binding properties and the electronic structures revealed that the cytophosphane molecule could be adsorbed on the SWCNT by the adsorption energy of approximately -100.3 kcal mol-1. Also, it was found that the electronic properties of the SWCNT are very sensitive to the presence of cytophosphane molecules so the energy gap of the nanotube is changed by about 61% after the adsorption process. Based on calculated results, the SWCNT is expected to be suitable as a drug carrier for delivering cytophosphane drugs.
Keywords: adsorption energy